From an idea to its realization: A new training centre at the institute for emergency medicine Belgrade - Anđelić Slađana; Čolaković Goran; Pavlović Aleksandar (Halo 194)
The idea to create a training centre at the Institute for Emergency Medicine Belgrade was conceived at an unofficial meeting between Prim. Dr Goran Čolaković, the Institute for Emergency Medicine in Belgrade (IEM) General Manager; Prof. Dr Sladjana Andjelić, the IEM Education Center Coordinator; and Prof. Dr Aleksandar Pavlović, the initiator and founder of the Center for Simulation at the University of Pristina Faculty of Medicine Pristina based in Kosovska Mitrovica towards the end of 2015. The need to create a training centre stems from the necessity to provide a contemporary approach to education in treating various emergency medical conditions. This vision requires a new spatial and technical structure with modern phantom mannequins (rescue dummies), medical devices, and equipment. Based on the project financed by the European Union and the European Bank for Reconstruction and Development (EBRD), the reconstruction of the IEM building with a 2000m2 training centre began in July 2021. The Centre aims to integrate all medical knowledge and skills necessary to treat emergency medical conditions in realistic scenarios. It will, therefore, have two simulation centres, five training rooms, two rooms containing vehicles and a large amphitheatre and library.